2019
DOI: 10.1186/s12888-018-1996-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychological distress of Bosnian war survivors: an 11-year follow-up of former displaced persons, returnees, and stayers

Abstract: BackgroundResearch on the long-term mental health consequences of war and displacement among civilians who live in post-conflict countries is rare. The aim of this study was to examine the developmental trajectories and predictors of general psychological distress in three samples of Bosnian war survivors over an 11-year period.MethodsIn 1998/99, about three years after the war in Bosnia and Herzegovina, a representative sample of 299 adult Sarajevo citizens was examined in three subsamples: individuals who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 29 publications
7
136
0
2
Order By: Relevance
“…Every participant saw this as a welcome addition. This finding was in accordance with those of Morton and colleagues [ 26 ] and Berry and colleagues [ 44 ]. These 3 suggestions may be used to strongly improve how beneficial and actionable an assessment tool such as the QoL-ME app is to patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Every participant saw this as a welcome addition. This finding was in accordance with those of Morton and colleagues [ 26 ] and Berry and colleagues [ 44 ]. These 3 suggestions may be used to strongly improve how beneficial and actionable an assessment tool such as the QoL-ME app is to patients.…”
Section: Discussionsupporting
confidence: 94%
“…Respondents also indicated that they were sometimes surprised by how high their scores were, which led to the insight that “things were not so bad.” Two participants indicated that they already had sufficient insight into their own quality of life and therefore derived no extra benefit from using the QoL-ME app. This finding echoed results found by Berry and colleagues [ 44 ], who investigated views on using digital self-management tools among people with severe mental health problems; a number of participants who contributed to that qualitative interview study indicated that they were already sufficiently self-aware and expected little benefit from using digital self-management tools [ 44 ].…”
Section: Discussionsupporting
confidence: 73%
“…The lack of an association between online socializing/surfing habits and PA in the regression analysis, might also be explained by the immediate and extensive accessibility of online activity to adolescents throughout the day. This 'all day online accessibility' would be possible via mobile smartphone use, and children aged 11 and older have previously been reported as having ubiquitous access to such devices [34]. This may create a scenario making an unaffected PA time allocation for adolescents plausible, although a moderate inverse association between smartphone use and PA has previously been shown in a similar population [35].…”
Section: Plos Onementioning
confidence: 99%
“…Excessive smartphone use among adolescents can interfere with concentration at school or work and can cause physical difficulties, such as neck stiffness, blurred vision, wrist or back pain, and sleep disturbances [ 11 , 12 , 13 , 14 ]. It can also reduce in-person social interaction and academic achievement and lead to mental health problems [ 11 , 14 , 15 ]. Therefore, smartphone overuse is a major problematic behavior issue to consider in adolescents.…”
Section: Introductionmentioning
confidence: 99%